Strategi Guru Dalam Mengatasi Bullying PadaSiswa Sekolah Dasar - Purnomo, Heru; Ningrum, Wiyanda Widya (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
This study aims to describe how the teacher's strategy is in overcoming bullying attitudes at SD Muhammadiyah Wonorjo. This type of research uses a qualitative approach with the case study method. The research location is SD Muhammadiyah Wonorjo 1 Sanden. Data collection techniques through observation, question and answer and documentation. Data were analyzed using data collection techniques, data presentation, inference and data validity. The results of the study show that the teacher's strategy in overcoming bullying behavior includes: (1) Finding out the cause of the problem in advance, (2) Giving punishment to each bully, (3) Giving verbal warnings, (4) Appeals or services , (5) Giving gifts (rewarding) and (6) Monitoring (monitoring). It is hoped that the different strategies used can change student behavior for the better.